GESTION ADMINISTRATIVA EN LA INDUSTRIA ARROCERA ‘‘DON ERNESTO - Palma Yturralde, Ufredo Ivan (2019)
Throughout history, one of the main pillars of the economy worldwide has been the primary sector, which has been complementing the industrial sector, but has not been fully exploited. The Rice Industry "Don Ernesto" will present serious problems in the future if the manager or owner fails to make good decisions for the efficient development of the industry. In the present case study, the absence of his administrator in the workplace in the Rice Industry "Don Ernesto" is reported. The location of the site is three posts 41 km. 1/2 of the Babahoyo Guayaquil highway, present certain problems that are detrimental to the development of this company, its activity is dynamic since it is a strategically propitious sector for its development, but it has not yet achieved efficiency in its entirety